MANAJEMEN PERPUSTAKAAN DALAM PENINGKATAN KUALITAS LAYANAN DAN MINAT BACA - Naimah Naimah (PASCASARJANA UNISNU, 2021)
Abstract: This research aimed to find out about library management which included planning, organizing, staffing, directing, and controlling for the improvement of service and students reading interest at SMPN 3 Salatiga. This research used qualitative approach. Type of this research was descriptive. The research was done in Adyama Pustaka Library of SMPN 3 Salatiga. Data was collected by observation, interview, and documentation. From the result of the research, it can be concluded that: 1) planning of library work program at SMPN 3 Salatiga is in accordance with the planning of library program which are purpose, policy, strategy, and program. All of formulated work program has described about the purpose, policy, strategy, and upcoming program to achieve the desire result. 2) Implementation of library work program at SMPN 3 Salatiga in improving the quality of service and reading interest includes; implementation of differentiation program, processing literature, implementation of service program, implementation of data analysis program, implementation of students activity program, implementation of promotion program, and implementation of inventory taking. The implementation of library work program at SMPN 3 Salatiga has been running well. Then, added by establishment with intern and extern part. 3) Evaluation of planning and implementation of library work program is as a basis for determining policies in the following year.Keywords: Service Quality; Library Management; Reading Interest